Validating a novel Attentional Bias Modification Task: The future may be in the cards - Notebaert, L.; Clarke, Patrick; Gafton, B.; MacLeod, C. (Elsevier, 2015)
Attentional bias modification (ABM) is a promising therapeutic tool aimed at changing patterns of attentional selectivity associated with heightened anxiety. A number of studies have successfully implemented ABM using the modified dot-probe task. However others have not achieved the attentional change required to achieve emotional benefits, highlighting the need for new ABM methods. The current study compared the effectiveness of a newly developed ABM task against the traditional dot-probe ABM task. The new person-identity-matching (PIM) task presented participants with virtual cards, each depicting a happy and angry person. The task encourages selective attention toward or away from threat by requiring participants to make matching judgements between two cards, based either on the identities of the happy faces, or of the angry faces. Change in attentional bias achieved by both ABM tasks was measured by a dot-probe assessment task. Their impact on emotional vulnerability was assessed by measuring negative emotional reactions to a video stressor. The PIM task succeeded in modifying attentional bias, and exerting an impact on emotional reactivity, whereas this was not the case for the dot-probe task. These results are considered in relation to the potential clinical utility of the current task in comparison to traditional ABM methodologies.